Dimeric Self-assembling via Hydrogen Bonding and Emissive Behavior of a New Copper (I) Complex - dos Reis, Juciely M.; Martins, Bruna F. R.; Favarin, Lis R. V.; Rosa, P. P.; Laranjeira, G. B.; Almeida, Cristiane F.; de Oliveira, Silvio Cesar; Pizzuti, Lucas; Machulek Júnior, Amilcar; Casagrande, Gleison Antônio (Orbital: The Electronic Journal of Chemistry, 2017)
This work describes the synthesis, structural characterization and emissive behavior of a new copper (I) complex based on 1-thiocarbamoyl-5-(4-methoxiphenyl)-3-phenyl-4,5-dihydro-1H-pyrazole ligand. A dimeric self-assembling via hydrogen bonding was determined by analyzing the short contacts present in the solid-state structure by means of X-ray crystallography. The spectroscopic properties were determined using UV-Vis and fluorescence experiments and an interesting behavior as bluish luminescence was assigned mainly to the mixed (MLCT + IL) electronic transitions of the Cu(I)d10 ® (S=C–Nligand) type. The complete characterization of the new copper (I) complex also included elemental analyses and IR spectroscopy.DOI: http://dx.doi.org/10.17807/orbital.v9i1.952